Ectomesenchymoma with Embryonal Rhabdomyosarcoma and Ganglioneuroma, Arising in Association with Benign Triton Tumor of the Tongue. (May 2014) - VandenHeuvel, Katherine A.; Carpentieri, David F.; Chen, Jie; Fung, Kar-Ming; Parham, David M.
Soft-tissue tumors known as "triton" tumors are rare lesions containing neural tissue and skeletal muscle at varying levels of maturity and malignant potential. Benign triton tumors, also called "neuromuscular choristomas" or "neuromuscular hamartomas, " consist of neural tissue containing mature skeletal muscle in intimate relationship with peripheral nerve. These tumors are rare in the head and neck in children. Ectomesenchymomas are similar tumors consisting of a malignant mesenchymal component, usually embryonal rhabdomyosarcoma, and a neuroectodermal component represented by mature ganglion cells or primitive neuroblastic/neuroectodermal foci (primitive ectomesenchymoma). Benign triton tumors have been regarded as benign, whereas ectomesenchymomas have been operationally considered to be variants of rhabdomyosarcoma. We present here a unique case that combines features of these 2 entities in a recurrent lesion on the tongue of a 35-month-old girl. This lesion raises questions about the "benign" nature of benign triton tumor and its possible relationship to ectomesenchymoma.